2020
DOI: 10.1109/taes.2019.2951186
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Low-Cost TMR-Without-Voter Based HIS-Insensitive and MNU-Tolerant Latch Design for Aerospace Applications

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 23 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…However, the latch cannot tolerate DNU because if the data that remain in the two feedback loops are flipped, the latch will propagate incorrect logical values. [13]; (b) HLDTL [14]; (c) NTHLTCH [15]; (d) DNCS-SEU [16]; (e) DNURL [17]; (f) DICE4TNU [18]; (g) TNUHL [19]; (h) SMNUT [20]; (i) TMHIMNT [21]; (j) LCTNUT [22].…”
Section: Snu-tolerant Latchesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the latch cannot tolerate DNU because if the data that remain in the two feedback loops are flipped, the latch will propagate incorrect logical values. [13]; (b) HLDTL [14]; (c) NTHLTCH [15]; (d) DNCS-SEU [16]; (e) DNURL [17]; (f) DICE4TNU [18]; (g) TNUHL [19]; (h) SMNUT [20]; (i) TMHIMNT [21]; (j) LCTNUT [22].…”
Section: Snu-tolerant Latchesmentioning
confidence: 99%
“…The TMHIMNT latch [21] consists of three clock-controlled DICE units, seven transmission gates, three inverters, and one clock-controlled inverter, as shown in Figure 2i. At the output end, the current competition is used to avoid the HIS generated when the C-element is used to tolerate fault.…”
Section: Tnu-tolerant Latchesmentioning
confidence: 99%
See 1 more Smart Citation
“…The research question addressed in this paper can be formulated as follows: Is it possible to obtain better classification accuracy and/or reduce the number of features by utilizing FA for feature selection in comparison to other available contemporary methods? Consequently, the , [12] , [13] major goal of the research proposed in this manuscript is to address the feature selection challenge further by achieving better classifications accuracy and/or to utilize a smaller number of features than other existing traditional and metaheuristics-based methods. From the literature survey, it also can be concluded that the potential of one of the most efficient swarm intelligence approaches, the firefly algorithm (FA), was not fully investigated for feature selection.…”
Section: Introductionmentioning
confidence: 99%
“…Jamil and Haleem 33 obtained unsteady motion of fractionalized magnetohydrodynamic Jeffrey liquid via porous plate with linear slip effect. The natural convection motion of non-Newtonian liquid via different surface was focused 34 36 . The convection motion via various sheets was explored 37 39 .…”
Section: Introductionmentioning
confidence: 99%